Interpretasi dan Kontroversi: Studi tentang Hakikat Insan Karya Ahmad Laksamana - Ibrahim, Nur Fadlina binti; Juwaini, Juwaini; Furqan, Furqan; HM. Yasin, Taslim (Program Studi Aqidah dan Filsafat Islam, 2023)
Haji Ahmad Laksamana, a controversial figure known through his work “Hakikat Insan”, is often considered deviant from traditional Islamic teachings, particularly regarding the use of Sharia and Tariqa as well as interpretations of the Quran. This article aims to describe the thoughts and Quranic interpretation methodology of Haji Ahmad Laksamana. This study employs a qualitative method with a literature analysis approach. The primary source is the text “Hakikat Insan,” supplemented by various secondary sources, including journals and relevant books. The study finds that Haji Ahmad Laksamana's teachings emphasize the recognition of the essence of knowledge to achieve the level of Insan Kamil Mukamil. His thoughts, reflected in discussions about the relationship between humans and Allah, the dignity of the soul, the essence of the testimony of faith, as well as concepts of Islam, faith, monotheism, and gnosis, demonstrate a unique approach. However, his interpretation method, such as translating Quranic verses into symbols, has sparked controversy and is considered deviant from traditional Islamic understanding. Haji Ahmad Laksamana's controversial ideas are viewed as contradictory to Islamic teachings, diminishing the honor of the Quran and Hadith.AbstrakHaji Ahmad Laksamana, seorang figur kontroversial yang dikenal melalui karyanya “Hakikat Insan” sering kali dianggap menyimpang dari ajaran Islam tradisional, terutama dalam hal penggunaan syariat dan tarekat serta penafsiran Al-Quran. Artikel ini bertujuan mendeskripsikan tentang pemikiran, dan metodologi penafsiran Al-Quran Haji Ahmad Laksamana. Kajian ini menggunakan metode kualitatif dengan analisis kepustakaan. Sumber utama adalah teks “Hakikat Insan” serta berbagai sumber sekunder termasuk jurnal dan buku yang relevan. Kajian ini menemukan bahwa ajaran Haji Ahmad Laksamana menitikberatkan pada pengenalan ilmu hakikat untuk mencapai tingkat Insan Kamil Mukamil. Pemikirannya yang tertuang dalam pembahasan mengenai hubungan manusia dengan Allah, martabat nafsu, hakikat syahadat, serta konsep Islam, iman, tauhid, dan makrifat, menunjukkan pendekatan yang unik. Namun, metode interpretasinya, seperti penerjemahan ayat Al-Quran ke dalam simbol, telah menimbulkan kontroversi dan dianggap menyimpang dari pemahaman Islam tradisional. Pemikiran Haji Ahmad Laksamana yang kontroversial dianggap bertentangan dengan ajaran Islam dan mengurangi kehormatan Al-Quran dan hadis.